Differential Item Functioning (DIF) Using Rasch Model in Diagnostic Test Instrument - Omar, Mohd Zaharuddin; Mahamod, Zamri (International Journal of Psychosocial Rehabilitation, 2020)
Detecting differential item is one way of determining the reliability of an instrument. The researcher used Rasch model (Differential Item Functioning Analysis – DIF) to identify the items which are gender- biased in the Diagnostic Test of Lower Secondary Bahasa Melayu System (DTLSBMS) instrument. Gender-biased detection is done on all items since the study found the existence of different academic performance based on gender and the analyses of public examination results like UPSR, PMR and SPM. Female students’ performance was better than male students. The items in the instrument should be fair to all test takers. This instrument has 289 items and six constructs which were verified by seven experts. The samples were 935 Form One students from ten districts in Pahang, Malaysia. Alpha Cronbach index values (KR20) for the whole items were 0.98 while the Alpha Cronbach index values for each construct was between 0.71 and 0.95. The result of the study found that four items of Morphology construct and two items of syntax had critical DIF t-value (more than ±2.0 logits) whereby the DIF contrast value was still at ±0.5. In short, UDSBMR instrument has good reliability and fairness as a diagnostic test tool.